2000
DOI: 10.1023/a:1026575619155
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity in Bilateral Breast Cancer

Abstract: Women who develop bilateral breast cancer at an early age are likely to harbour germline mutations in breast cancer susceptibility genes. The aim of this study was to test for concordant genetic changes in left and right breast cancer of young women (age < 50) with bilateral breast cancer that may suggest an inherited breast cancer predisposition. Microsatellite markers were used to test for loss of heterozygosity (LOH) in left and right tumours for 31 women with premenopausal bilateral breast cancer. Markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
1
25
0
2
Order By: Relevance
“…Thus, in germline mutation carriers, tumor progression depends on loss of the wild-type allele, often molecularly detectable as loss of heterozygosity (LOH) 17,18 . However, LOH at the BRCA1 and BRCA2 loci has been detected in 20% and 70% of sporadic breast and ovarian cancers respectively, leaving open the possibility that these two susceptibility genes could be involved in a proportion of breast cancer in non-mutation carriers [17][18][19][20][21] . In this study we evaluated the distribution of molecular subtypes of breast tumors in a group of very young Brazilian women using an immunohistochemical panel of biomarkers on tissue microarray (TMA) to address the frequency of basallike carcinomas among this special group of women with breast cancer.…”
Section: Artigo Original Introductionmentioning
confidence: 99%
“…Thus, in germline mutation carriers, tumor progression depends on loss of the wild-type allele, often molecularly detectable as loss of heterozygosity (LOH) 17,18 . However, LOH at the BRCA1 and BRCA2 loci has been detected in 20% and 70% of sporadic breast and ovarian cancers respectively, leaving open the possibility that these two susceptibility genes could be involved in a proportion of breast cancer in non-mutation carriers [17][18][19][20][21] . In this study we evaluated the distribution of molecular subtypes of breast tumors in a group of very young Brazilian women using an immunohistochemical panel of biomarkers on tissue microarray (TMA) to address the frequency of basallike carcinomas among this special group of women with breast cancer.…”
Section: Artigo Original Introductionmentioning
confidence: 99%
“…15 Accumulating literature presents contradicting results. 11,[17][18][19][20][21][22][23][24][25] Some authors have demonstrated similarity in histologic subtype, 12,23 tumor grade, 17 and hormone receptor status 16,18 between the two tumors, suggesting a single-cell origin, whereas others had different results. 25 In addition, similar mammographic appearance may be seen in bilateral breast carcinomas with a mirror image location.…”
mentioning
confidence: 99%
“…26,27 Neither clinical nor histopathologic features can definitively determine the relationship between multiple deposits of breast cancer at the individual patient level with certainty. Using molecular techniques, few studies showed the presence of similarities in bilateral breast cancer, indicating that these carcinomas may result from a metastatic event, 11,24 while other investigators present evidence for the independent pathogenesis in majority of these tumors. 16,[19][20][21][22]25 This controversy reflects the lack of a definitive methodology to distinguish de novo primary from metastatic tumor deposition.…”
mentioning
confidence: 99%
“…Six years ago, the human breast cancer susceptibility gene Brca2 was identified [22,23]. After sequencing the full-length cDNA, many reports described mutational analyses of the gene in families and in primary tumors [7,9,19]. The Brca2 gene consists of 27 exons, which encode an 11-to 12-kb transcript.…”
mentioning
confidence: 99%